Platelet activation: a promoter for psoriasis and its comorbidity, cardiovascular disease - Jiang, Ziqi; Jiang, Xiaoran; Chen, Aijun; He, Wenyan (Frontiers in Immunology, 2023)
Psoriasis is a chronic inflammatory skin disease with a prevalence of 0.14% to 1.99%. The underlying pathology is mainly driven by the abnormal immune responses including activation of Th1, Th17, Th22 cells and secretion of cytokines. Patients with psoriasis are more likely to develop cardiovascular disease (CVD) which has been well recognized as a comorbidity of psoriasis.As mediators of hemostasis and thromboinflammation, platelets play a n important part in CVD. However, less is known about their pathophysiological contribution to psoriasis and psoriasis-associated CVD. A comprehensive understanding of the role of platelet activation in psoriasis might pave the path for more accurate prediction of cardiovascular (CV) risk and provide new strategies for psoriasis management, which alleviates the increased CV burden associated with psoriasis. Here we review the available evidence about the biomarkers and mechanisms of platelet activation in psoriasis and the role of platelet activation in intriguing the common comorbidity, CVD. We further discussed the implications and efficacy of antiplatelet therapies in the treatment of psoriasis and prevention of psoriasis-associated CVD.